Implementing Soft-Power as an Experiential Learning Strategy to Enhance Speaking Engagement: A Case Study in a Thai School - Wulandari, Diah Ayu Rizqi; Maghfiroh, Ana; Harmanto, Bambang; Sinthong, Phakit; Simpol, Wanida (Journal of Languages and Language Teaching, 2025)
English language teaching in Thailand faces persistent challenges, including barriers related to teacher competence, insufficient English fluency, and a lack of effective teaching methods and strategies. Socio-individual and cultural factors, such as low self-esteem, also reduce students’ motivation in speaking practice. This study explores how the Soft-power strategy can address these issues by emphasizing active participation, collaborative learning, and experiential techniques like group discussions and real-life conversations that foster a supportive classroom environment. Using a qualitative descriptive design, the study involved 15 fourth-grade students over three months. Data were collected through classroom observations and questionnaires. The findings show that Soft-power strategies significantly enhanced student engagement. For instance, more than 86% of participants strongly agreed that the strategy helped them build confidence in speaking English, while over 66% reported enjoying and feeling comfortable during the activities. The analysis also revealed reduced student anxiety and more positive peer interactions. The results suggest that Soft-power strategies offer a promising alternative to traditional methods by fostering a supportive learning environment for long-term language development. These findings offer valuable insights for educators and policymakers aiming to transform English instruction in non-native, multilingual settings.